Integrated power and attitude sensors tile for a small spacecraft - Zainab Mousawi; Anwar Ali; Muhammad Rizwan Mughal; Shoaib Ahmed Khan; Augustine Egwebe (Results in Engineering)
In pursuit of compact, redundant and miniaturized subsystems for nanosatellites, this paper introduces the design of a Hexagonal Power Management and Attitude Sensor Tile (HPMAST), a multifunctional unit integrated into an hexagon-shaped spacecraft. Six HPMAST tiles are mounted on the external periphery of the spacecraft. Each HPMAST tile combines high-efficiency solar energy harvesting, power conversion with localized maximum power point tracking (MPPT), and attitude determination capabilities within a tightly packed eight-layer PCB structure. The power subsystem features a hysteresis-controlled boost converter that raises the 19.8 V input, generated from 36 photovoltaic cells arranged as four parallel strings of nine series-connected 2.2 V cells, to a regulated 28 V Power Distribution Bus (PDB). Each HPMAST tile with dimensions 16.5 cm x 99 cm produces 36 W, with conversion and control circuitry located on the panel's backside. Embedded within four internal PCB layers is a reconfigurable planar magnetorquer coil, designed for torque generation through its interaction with the Earth’s magnetic field. The tile also houses miniature attitude sensors, including a gyroscope, magnetometer, and sun sensor, enabling localized three-axis attitude sensing. While the HPMAST tile primarily manages the power harvesting, conversion, and distribution subsystems of the hexagonal-shaped spacecraft, the integration of attitude sensing and actuation ensures scalability, compactness and provides more space for the payload. Findings from this work show that the proposed system achieved stable and efficient power regulation in simulation, with the hysteresis-based MPPT boost converter delivering a regulated 28 V output and maintaining voltage ripple within 0.2 V. The system achieved a peak efficiency of 93 % under standard input conditions. The embedded magnetorquer exhibited a magnetic dipole moment of 0.415 A·m² while maintaining thermal limits in the hybrid configuration. These results validate the technical feasibility and robustness of the HPMAST tile for future in-orbit deployment. In addition to power and attitude determination systems, ongoing work will focus on the thermal and magnetic characterization of the embedded coil to support future in-orbit deployment.